An epididymis-specific secretory protein HongrES1 critically regulates sperm capacitation and male fertility. - Yuchuan Zhou (Public Library of Science (PLoS), 2008)
Mammalian sperm capacitation is an essential prerequisite to fertilizion. Although progress had been made in understanding the physiology and biochemistry of capacitation, little is known about the potential roles of epididymal proteins during this process. Here we report that HongrES1, a new member of the SERPIN (serine proteinase inhibitor) family exclusively expressed in the rat cauda epididymis and up-regulated by androgen, is secreted into the lumen and covers the sperm head. Co-culture of caudal sperms with HongrES1 antibody in vitro resulted in a significant increase in the percentage of capacitated spermatozoa. Furthermore, the percentage of capacitated spermatozoa clearly increased in rats when HongrES1 was down-regulated by RNAi in vivo. Remarkably, knockdown of HongrES1 in vivo led to reduced fertility accompanied with deformed appearance of fetuses and pups. These results identify HongrES1 as a novel and critical molecule in the regulation of sperm capacitation and male fertility.